Children-Dietary Inflammatory Index (C-DII), cardiometabolic risk, and inflammation in adolescents: a cross-sectional study - Yilmaz, Feray Cagiran; Acik, Murat (Walter de Gruyter Gmbh, 2022)
Objectives There is limited evidence about the inflammatory potential of diet and cardiometabolic risk in children. The aim of this study was to evaluate the association between the Children's Dietary Inflammatory Index (C-DII) with cardiometabolic risk factors in Turkish adolescents from 10 to 17 years. Methods Participants aged 10-17 years, who completed a 24-h dietary recall, from which C-DII scores were calculated, were include in this cross-sectional study. Lipid profile, glycemic parameters, high-sensitivity C-reactive protein (hs-CRP), liver enzymes, thyroid-stimulating hormone (TSH), and uric acid were analyzed in blood samples. Sociodemographic characteristics and sedentary behavior were assessed using a semi-structured questionnaire. We compared the distributions of anthropometric, biochemical, and blood pressure measurement levels associated with cardiometabolic risk factors by the median of C-DII with linear regression. Results The mean sample C-DII was -0.16 +/- 2.31 and ranged from -3.22 to +4.09. Higher median C-DII scores, indicating a more pro-inflammatory diet among children, were associated with higher blood pressure and body mass index (BMI). However, the C-DII was modestly directly associated with fasting insulin, fasting blood glucose, and waist circumference. The area under the receiver operating curve of C-DII in predicting hs-CRP was found to be quite high (0.864, 95% CI: 0.795-0.933). Conclusions Consuming a pro-inflammatory diet in adolescence was associated with alterations in cardiometabolic risk factors, especially with systolic blood pressure, diastolic blood pressure, and BMI.
Keywords: adolescent; blood pressure; cardiometabolic risk; children's dietary inflammatory index; C-reactive protein